BS EN 4708-204. Aerospace series. Sleeves, heat-shrinkable, for binding, insulation and identification. Part 204. Limited fire hazard identification sleeves. Operating Temperature range -40°C to 105°C. Product Standard (19th July 2021) - British Standards Institution,
No abstract available